Prevalence of strabismus and its risk factors among school aged children: The Hong Kong Children Eye Study - Xiu Juan Zhang (Nature Portfolio, 2021)
Abstract The study aims to determine the prevalence of strabismus and its risk factors among school children in Hong Kong. This is a cross-sectional study involving 6–8 year old children from different districts in Hong Kong. 4273 children received comprehensive ophthalmological examination, cycloplegic auto-refraction, best corrected visual acuity (BCVA), anterior segment examination, cover/uncover test, ocular motility, and fundus examination. Demographic information, pre- and post- natal background, parental smoking status, and family history of strabismus were obtained through questionnaires. Strabismus was found among 133 children (3.11%, 95% CI 2.59–3.63%), including 117 (2.74%) exotropia and 12 (0.28%) esotropia cases (exotropia-esotropia ratio: 9.75:1). There was no significant difference in prevalence across age (6–8 years) and gender. Multivariate analysis revealed associations of strabismus with myopia (≤ − 1.00D; OR 1.61; 95% CI 1.03–2.52; P = 0.037) hyperopia (≥ + 2.00D; OR 2.49; 95% CI 1.42–4.39; P = 0.002), astigmatism (≥ + 2.00D; OR 2.32; 95% CI 1.36–3.94; P = 0.002), and anisometropia (≥ 2.00D; OR 3.21; 95% CI 1.36–7.55; P = 0.008). Other risk factors for strabismus included maternal smoking during pregnancy (OR 4.21; 95% CI 1.80–9.81; P = 0.001), family history of strabismus (OR 6.36; 95% CI 2.78–14.50, P < 0.0001) and advanced maternal age at childbirth (> 35 years; OR 1.65; CI 1.09–2.49, P = 0.018). The prevalence of strabismus among children aged 6—8 years in Hong Kong is 3.11%. Refractive errors, family history of strabismus and maternal smoking history during pregnancy are risk factors. Early correction of refractive errors and avoidance of maternal smoking during pregnancy are potentially helpful in preventing strabismus.